1997
DOI: 10.1109/66.572084
|View full text |Cite
|
Sign up to set email alerts
|

Semi-empirical neural network modeling of metal-organic chemical vapor deposition

Abstract: Metal-organic chemical vapor deposition (MOCVD)is an important technique for growing thin films with various applications in electronics and optics. The development of accurate and efficient MOCVD process models is therefore desirable, since such models can be instrumental in improving process control in a manufacturing environment. This paper presents a semiempirical MOCVD model based on "hybrid" neural networks. The model is constructed by characterizing the MOCVD of titanium dioxide (TiO 2 ) films through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The function of each neuron is to compute the weighted sum of its inputs and determine its activation level using a nonlinear transfer function. This can be expressed analytically as (9) where is the synaptic weight, is the input, and is the output corresponding to the th neuron in the th layer. The nonlinear activation function used to determine the output of each neuron enables neural networks to generalize with a degree of freedom not available in statistical techniques [8].…”
Section: A Standard Neural Network Algorithmmentioning
confidence: 99%
“…The function of each neuron is to compute the weighted sum of its inputs and determine its activation level using a nonlinear transfer function. This can be expressed analytically as (9) where is the synaptic weight, is the input, and is the output corresponding to the th neuron in the th layer. The nonlinear activation function used to determine the output of each neuron enables neural networks to generalize with a degree of freedom not available in statistical techniques [8].…”
Section: A Standard Neural Network Algorithmmentioning
confidence: 99%
“…• Step 4: At th run, update the feedforward neural network process model by adaptation law (8) with the new data set. • Step 5: After the feedforward process model has been updated, use adaptation law (12) to calculate the new weights for the uniformity controller based on the estimate of removal rate profile and then go to step 3.…”
Section: B Training Algorithmmentioning
confidence: 99%
“…For the neural network based controller, we can obtain the optimized recipe by learning law given by (12) as - (15) Some experiments using -were tested. We found that the process performance under recipe -was not satisfactory.…”
Section: Performance Of the Neural Network Based Controllermentioning
confidence: 99%
See 2 more Smart Citations